Mistakes in Writing Narrative Texts Made by The Students of Senior High School - Dian Luthfiyati; Mohammad Adnan Latief; Suharmanto Suharmanto (Pascasarjana UM, 2015)
Abstract: This study was aimed at describing the errors in writing narrative texts made by the stu-dents of SMAN 2 Lamongan. The study employed descriptive cross-sectional quantitative research design. The subjects of this study were students from grade X, XI, and XII of SMAN 2 Lamongan. The main instruments of the study were the writing prompt and narrative guidelines. The students’ writings were scored based on the scoring scale adapted from Cohen and Coffin, et.al; Hyland. The findings showed that the students made errors in moral value, content, organization, grammar, and vocabulary. Grammar is a dominant error because it is found in each grade and each program. The most dominant error in grammar was simple past tense. Key Words: error, narrative writingAbstrak: Penelitian ini bertujuan untuk menggambarkan kesalahan dalam menulis teks naratif yang dibuat oleh siswa SMAN 2 Lamongan. Penelitian ini menggunakan desain penelitian cross-sectional kuantitatif deskriptif. Subyek penelitian ini adalah siswa dari kelas X, XI, dan XII SMAN 2 Lamongan. Instrumen utama dari penelitian ini adalah writing prompt dan narrative guidelines. Tulisan-tulisan siswa dinilai berdasarkan skala penilaian yang diadaptasi dari Cohen dan Coffin, dkk.; Hyland. Te-muan menunjukkan bahwa siswa membuat kesalahan pada nilai moral, isi, organisasi, tata bahasa, dan kosa kata. Tata bahasa merupakan kesalahan yang paling dominan karena ditemukan di setiap kelas dan setiap program. Kesalahan yang paling dominan dalam tata bahasa adalah kesalahan ben-tuk simple past tense.Kata kunci: kesalahan, tulisan naratif